Model Manajemen Kelas Talaqi dengan Pendekatan Metode Tabarak pada Rumah Qur’an Ghazzah el-Izzah kota Palembang - Maida Rinawati; Muhammad Win Afgani; Afriantoni Afriantoni (Departement of Mathematics Education, 2024)
Rumah Qur'an Ghazzah el-Izzah is a da'wah institution oriented towards Al-Qur'an education with takhassus and general education programs, diniyah and regular tahfizh. In implementing the tahfizh Al-Qur'an program, Rumah Qur'an Ghazzah el-Izzah implements management functions consisting of planning, organizing, directing and controlling. However, many students are unable to achieve the target of memorizing the Al-Qur'an according to the provisions that have been set. Therefore, by using management analysis the author can find out the application of management functions at the Ghazzah el-Izzah Qur'an House in developing students to memorize verses of the Qur'an in certain ways and continuously. This research uses a qualitative approach with phenomenological methods. The data sources in this research are based on primary and secondary data. In determining the data source, the author uses the snowball sampling technique, namely taking data sources that are initially small in amount and then become large. Data was obtained from respondents using interviews in the form of guided interviews, observation and documentation. Meanwhile, the data analysis that the author uses is analysis carried out simultaneously with data collection. The analysis process is deductive, namely starting from general conclusions or generalizations which are described into concrete examples or facts to explain the conclusions or generalizations. Based on the research results obtained by the author, the application of four management functions, namely planning, organizing, directing and supervision in implementing the Al-Qur'an tahfizh program at the Ghazzah el-Izzah Qur'an House cannot be said to be running optimally, especially in the monitoring or evaluation function. This causes many students to not be able to achieve the memorization target in accordance with the provisions that have been set. The results of the monthly evaluation stated that only 44% of students were able to achieve the memorization target. This is due to the system of evaluating/measuring the results of students' memorization which is implemented by the students instead of depositing memorization according to the target but rather students depositing memorization according to the limits of their abilities, and also the limited assatidz so that large halaqah groups are formed, namely these groups consist of 20 students. or even more.